Pengaruh Literasi Keuangan, Parental Income, dan Teman Sebaya Terhadap Financial Behavior dengan Self-Control Sebagai Moderasi - Nur Laila Qomariyah; Sri Padmantyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the influence of financial literacy, parental income, and peer influence on students' financial behavior with self-control as a moderating factor. The research approach used is quantitative through a survey method of 100 students from the Faculty of Economics and Business, Muhammadiyah University of Surakarta. Research data were obtained through validity and reliability tests. The analysis was carried out using multiple linear regression and moderation tests. The results of the study indicate that financial literacy, parental income, and peers have a significant effect on students' financial behavior. Someone with high financial literacy tends to be better able to manage their finances. Parental income also has a significant impact, where students from families with higher incomes have wider means of financial capacity, although in some cases it can increase consumptive behavior. Peers also have a strong influence on students' financial behavior, because they often imitate consumption patterns in their environment. Furthermore, self-control strengthens the relationship between the influence of financial literacy, parental income, and peers on financial behavior. Students who have better self-control can avoid consumptive behavior and manage their finances more wisely. Therefore, increasing financial literacy needs to be accompanied by strategies to strengthen self-control so that students can make more optimal financial decisions.